Tuesday

July 29, 2014

July 29, 2014

Posted by **Deborah** on Tuesday, January 29, 2013 at 11:08am.

5x^2(2x – 3)

5x^2 + 2x – 3

10x^3 – 15x^2

–5x^2

7x^3 – 15x^2

2. What is the GCF of the terms of 8c^3 + 12c^2 + 10c ?

2

4

2c

4c

3. How can the polynomial 6d^4 + 9d^3 – 12d^2 be factored?

3d^2(2d^2 + 3d – 4)

3d^2(3d^2 + 6d – 9)

3d(d^3 + 3d^2 – 4)

6d^2(d2 + 3d^3 - 6

4. There is a circular garden in the middle of a square yard. The radius of the circle is 4x. The side length of the yard is 20x. What is the area of the part of the yard that is not covered by the circle?

4x(5)

8x^(5 – Pie sysmbol)

16x(25 + Pie Symbol)

16x2(25 – Pie Symbol )

5. What is the simplified form of –3z^2(z + 2) – 4(z2 + 1)?

–7x^2 + 1

–3z^3 – 4z^2 – 6z – 4

–3z^3 – 2z^2 – 4

–3z^3 – 10z^2 – 4

Answers:

1.)B

2.)C

3.)A

4.)D

5.)D

Thank You

- Math: Check Answers -
**visoth**, Tuesday, January 29, 2013 at 11:11amyou hvae math check answers on the title but you didnt even pick answers you jsut asking us to do your homework for you

- Math: Check Answers -
**visoth**, Tuesday, January 29, 2013 at 11:12amim sorry i didnt see the bottom part i take that back

- Math: Check Answers -
**visoth**, Tuesday, January 29, 2013 at 11:14ami didnt check number 4 but the others should be right

- Math: Check Answers -
**Deborah**, Tuesday, January 29, 2013 at 11:34amThank You.

**Related Questions**

Math(Please check my work.) - (2x-3)(x^2+5x-3)=2x+10x^2-15x+9 *Is this correct...

algbrea - 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -...

math - Solve by elimination 5x+y=2 3x+y=1 This is what I got : 3(5x+y=2) -5(3x+y...

grade nine math Polynomials - Mr. Smart just bought a new dog named Fluffy. Mr ...

MATH please help - 5xy^2 + 15x^2y^2 - 25xy^2 + 65x^2y^2 = 10x^2y^2 + 45xy^2 ...

MATH please help - 5xy^2 + 15x^2y^2 - 25xy^2 + 65x^2y^2 = 10x^2y^2 + 45xy^2 ...

MATH please help - 5xy^2 + 15x^2y^2 - 25xy^2 + 65x^2y^2 = 10x^2y^2 + 45xy^2 ...

Math - f(x)=13x^2 -15x-14 g(x)=15x^3+14x^2-15x+12 find f(3) × f(10) + f(-7) × g(...

Math - f(x)=13x^2 -15x-14 g(x)=15x^3+14x^2-15x+12 find f(3) × f(10) + f(-7) × g(...

algebra - -15(3+x)=-6x-9 -45-15x=-6x-9 -45-15x+15x=-6x+-15x-9 -45=21x-9 -45=x-9...